Flexibility of the Merdeka Curriculum in Giving Educators Freedom to Design Learning - Nailur Rosyida (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
The Merdeka Curriculum was introduced to provide educators with the flexibility to design learning activities tailored to students' needs. This study examines the transformation of the Merdeka Curriculum as an enhancement of the 2013 Curriculum, highlighting its flexibility in preparing lesson plans (RPP), integrating technology, and adopting innovative learning models such as Blended Learning, Flipped Classroom, and Project-Based Learning. The findings indicate that the Merdeka Curriculum enhances learning quality through adaptation to student characteristics but faces implementation challenges, including limited resources, lack of understanding, and infrastructure disparities. Proposed solutions include teacher training, the development of assessment instruments, and effective coordination among stakeholders. By addressing these challenges, the Merdeka Curriculum is expected to serve as a significant step in Indonesia's education reform toward achieving its golden generation.